(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The designation of water conservation areas, including the Wakatobi National Park (TNW), causes conflicts of interest, namely the interests of conservation and the interests of access to the utilization of marine resources. The access of residents in the Marine Protected Area (KKP) of TNW to utilize marine resources is limited by the existence of conservation regulations. The study aims to understand efforts to meet the needs of the population in the WTN MPA which can be used as material for consideration in the management of the WNP MPA. Information was collected through interviews and Focus Group Discussion (FGD) with a questionnaire tool. The study findings show that in meeting the necessities of life, residents in villages are affectedby the KKP TNW mostly by catching marine biota. These livelihoods are more influenced by natural factors (natural capital)and cultural factors. As the main source of livelihood for the majority of the population, fishing for marine biota is a source of conflict in the WNP MPA. Moreover, with the increasing population and the lack of alternative livelihoods, the decrease in the catch of marine biota will encourage fishermen to use more destructive fishing methods, and this is a violation of conservation regulations. For this reason, a new type of livelihood is needed that can reduce pressure on marine resources and is sustainable.